Patterns of Reactions to Red Pigment Tattoo and Treatment Methods. Issue 1 (March 2016) - Forbat, Emily; Al-Niaimi, Firas
Abstract Tattoos are common and used extensively as either body art or cosmetic make-up; more rarely, they can be traumatic in nature. We have systemically analysed the literature for the patterns of red pigment tattoo reactions and their treatment options. Our search identified 18 articles; there was 1 non-randomised controlled trial, and the rest were small case studies. In total 139 patients were included within the studies. This review systematically analyses the different subsets of red tattoo reactions including lichenoid, dermatitis, granulomatous, pseudolymphomatous and miscellaneous reactions. The current evidence for the treatment for the above is presented. Dermatitis and lichenoid reactions appear to be the most common subtype of red pigment reactions with various treatment methods applied showing laser intervention to have some degree of success.